Bidirectional universal dynamics in a spinor Bose gas close to a nonthermal fixed point - Schmied, Christian-Marcel; Prüfer, Maximilian; Oberthaler, Markus K.; Gasenzer, Thomas (Physical review, 2019)
We numerically study the universal scaling dynamics of an isolated one-dimensional ferromagnetic spin-1 Bose gas. Preparing the system in a far-from-equilibrium initial state, simultaneous coarsening and refining is found to enable and characterize the approach to a nonthermal fixed point. A macroscopic length scale which scales in time according to LΛ(t)∼tβ, with β≃1/4, quantifies the coarsening of the size of spin textures. At the same time kinklike defects populating these textures undergo a refining process measured by a shrinking microscopic length scale Lλ∼tβ′, with β′≃−0.17. The combination of these scaling evolutions enables particle and energy conservation in the isolated system and constitutes a bidirectional transport in momentum space. The value of the coarsening exponent β suggests the dynamics to belong to the universality class of diffusive coarsening of the one-dimensional XY model. However, the universal momentum distribution function exhibiting nonlinear transport marks the distinction between diffusive coarsening and the approach of a nonthermal fixed point in the isolated system considered here. This underlines the importance of the universal scaling function in classifying nonthermal fixed points. Present-day experiments with quantum gases are expected to have access to the predicted bidirectional scaling.